2008
DOI: 10.1152/ajplung.90224.2008
|View full text |Cite
|
Sign up to set email alerts
|

EGF and K+ channel activity control normal and cystic fibrosis bronchial epithelia repair

Abstract: Trinh NT, Privé A, Maillé E, Noël J, Brochiero E. EGF and K ϩ channel activity control normal and cystic fibrosis bronchial epithelia repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
121
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(140 citation statements)
references
References 56 publications
17
121
0
2
Order By: Relevance
“…This suggests a negatively charged inside and a positively charged outside that can be adjusted by an active transport of Na þ ions, simple diffusion, or pumping excess ions out of the cell. K þ channels play roles in stem cell differentiation and in left-right patterning of Xenopus embryos (Morokuma et al, 2008a,b), branchial epithelia repair (Trinh et al, 2008), epithelial wound healing (Lotz et al, 2004), myoblast migration (van Lunteren et al, 2002), embryonic spinal neuron activity (Chang and Spitzer, 2009), and neuronal signaling in Xenopus embryos (Gravagna et al, 2008). We found that K þ levels do not vary within B-S-T regions, in both amputated and uncut tails.…”
Section: Developmental Dynamicsmentioning
confidence: 53%
“…This suggests a negatively charged inside and a positively charged outside that can be adjusted by an active transport of Na þ ions, simple diffusion, or pumping excess ions out of the cell. K þ channels play roles in stem cell differentiation and in left-right patterning of Xenopus embryos (Morokuma et al, 2008a,b), branchial epithelia repair (Trinh et al, 2008), epithelial wound healing (Lotz et al, 2004), myoblast migration (van Lunteren et al, 2002), embryonic spinal neuron activity (Chang and Spitzer, 2009), and neuronal signaling in Xenopus embryos (Gravagna et al, 2008). We found that K þ levels do not vary within B-S-T regions, in both amputated and uncut tails.…”
Section: Developmental Dynamicsmentioning
confidence: 53%
“…Short-circuit currents (Isc) [30][31][32] were measured through CFBE and primary airway cells [28] that had been cultured on coated permeant filters until they reached an air-liquid interface and formed a polarised epithelium with high resistance [33,34]. Measurements were performed (see supplementary material for details) on intact monolayers or through apical membranes after permeabilisation of the basolateral side with 7.5 µM amphotericin B (Sigma-Aldrich), in the presence of a symmetrical physiological solution or a chloride (Cl − ) gradient, as indicated in figure legends.…”
Section: Electrophysiologymentioning
confidence: 99%
“…It has been reported that levels of LXA 4 are reduced in CF airways (19). These observations suggest that the reduced capacity for epithelial repair described in the CF epithelium may be exacerbated or caused by low levels of LXA 4 (1,19,45).…”
mentioning
confidence: 92%
“…Repeated insults to the airway epithelium result in damage and remodeling of the airway, resulting in a decline in lung function (33,34). Epithelial repair is triggered to restore the epithelial airway architecture; however, recent research suggests that this process is impaired in CF epithelial cells (16,27,44,45).…”
mentioning
confidence: 99%